A nonadiabatic oscillation study of DB white dwarfs - Gautschy, Alfred (2002)
A self-consistent abundance diffusion treatment in the evolution of cooling white dwarfs permitted a study of the effect of elemental segregation in nonadiabatic, nonradial stability computations. In particular, mode trapping manifesting itself in cyclically varying period separations behaved differently from its appearance in the damping/excitation rates. Another aspect of the investigation concerned the effect of heavy-element traces in homogeneous DB white-dwarf envelopes on their pulsational instability domain. The stellar models are computed with the CGM convection approach; the study can therefore be considered as a test of its performance in nonradial stability analyses.